Japan and the international monetary system - Nobumitsu Kagami (Intereconomics, 1980)
The 1970s saw the recurrence of major turmoil in the international monetary scene in which Japan played no small part. Japan's response to past monetary upheavals has always been passive and there were occasions when its passivity and delayed response so undermined the working of the monetary system that an eventual explosion became inevitable. This article tries to trace the underlying causes of Japan's behavioural pattern in an international monetary sphere and identify positive roles it can and should play against the background of a likely revolution in the international monetary system in the future. *** DIRECT SUPPORT *** A02GP009 00002
Keywords: 330; Monetary Policy